Analysis of the dynamic cutting force coefficient - Rao, Surendra B. (My University, 1977)
Conclusive evidence is presented in this thesis that the Dynamic Cutting Force Coefficients, as measured by the Double Modulation Method, do indeed represent the transfer function of the cutting process. Limits of stability, computed from the measured DCFCs for various steels and the measured transfer function of a lathe, are arrived at and compared with the experimental b_lim obtained, with these same steels, under similar cutting conditions on the same lathe.
A physical model to explain the DCFCs of Inner Modulation is presented. Mathematical relations are derived to correlate stable cutting forces with DCFCs of Inner Modulation. Tests results of stable cutting forces are presented from which the DCFCs of Inner Modulation are obtained using the above mentioned mathematical obtained DCFCs of Inner Modulation is presented to show the validity of the proposed model.
Keywords: Engineering; Engineering